Analisis Trend dan Ekspor Kelapa Indonesia di Pasar China - Sa'adah, Fachriyah; Relawati, Rahayu; Tain, Anas (Universitas Galuh, 2025)
Indonesia is the world's first largest coconut exporter. Coconut exports to China have the potential to increase the international market, know price competition, and gain benefits for the country. This research has the objectives; 1) analyze Indonesia's coconut production trends, Indonesia's coconut export trends in the form of export volume and Indonesia's coconut export value 2) analyze the projection of Indonesia's coconut production trends, coconut export volume and Indonesia's export value in the next 3 years. The data used is secondary data obtained from the Central Statistics Agency (BPS) from 2014 - 2023. The method used is trend analysis. The results of the study show that Indonesia's coconut production is experiencing a downward trend caused by the reduction of coconut plantation land in Indonesia and the number of damaged land and old coconut trees, while Indonesia's coconut export volume is experiencing an upward trend influenced by the rupiah currency exchange rate against the dollar, and the value of coconut exports is experiencing an upward trend caused by an increase in export volume, namely if the value of foreign currency strengthens the exchange rate and A weakening domestic currency will affect the increase in the value of Indonesia's coconut exports. After being forecast for the next 3 years, Indonesia's coconut production tends to decline every year. Meanwhile, the export volume and value of Indonesia's coconut exports to China have increased every year.